The influence of interest rate risk on efficiency in rural banks: The moderating role of loan distribution - Meliza Meliza; Zahro Zahro (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2021)
Interest rate fluctuations lead to movements in both rural banks’ lending and savings rates. These movements can result in interest rate risk affecting the efficiency of rural banks. The continuity of rural banks is vital because they are one of the financial institutions that funding financing for small and medium enterprises (SMEs). Thus, this study aims to analyse the influence of interest rate risk on the efficiency of rural banks in Indonesia from 2014 to 2018. Moreover, this study also investigates the role of the loan distribution as a moderating variable of the relationship between interest rate risk and efficiency. This research applies two stages of analysis. The first stage of analysis is estimating the efficiency score using Data Envelopment Analysis (DEA). The second stage measures the relationship between interest rate risk and efficiency and the role of loan distribution as a moderating variable using Tobit Regression. The regression analysis shows that interest rate risk has a positive and significant effect on efficiency. In addition, the loan distribution can enhance the relationship between interest rate risk and efficiency.Keywords: Efficiency; interest rate risk; loan distributionTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//